Alkoxysilane effect in hybrid material: A comparison of pHEMA-TiO2 and pMAPTMS-TiO2 nanoparticulate hybrids. (June 2019) - Gorbovyi, P.; Diaz-Gomez, A.P.; Traore, M.; Museur, L.; Rozes, L.; Ribot, F.; Sanchez, C.; Kuznetsov, A.I.; Chichkov, B.N.; Kanaev, A.
Graphical abstract: Photo-darkening kinetics (excitation with 25 ps pulsed of 5 mJ/cm 2 fluence at 355 nm) and 2-photon laser structuring (femtosecond Ti-sapphire, 800 nm) of HEMA-TiO2 and MAPTMS-TiO2 hybrids X10. The black cloud shows a damage of the structure appeared during the writing process in HEMA-TiO2 hybrids. Highlights: HEMA monomers form strong covalent bonds with TiO2 nanoparticles surface. MAPTMS monomers are not bound to the surface of TiO2 nanoparticles. Photochromic response of pHEMA-TiO2 is stronger than that of pMAPTMS-TiO2 . pHEMA-TiO2 hybrids are suitable for 2D/3D micropatterning. pMAPTMS-TiO2 hybrids are suitable for 2D/3D micromachining. Abstract: We report on a comparative study of photonic sensitivities of organic-inorganic hybrids prepared with size-selected 5 nm titanium-oxo-alkoxo nanoparticles and two different organic phases: HEMA (2-hydroxyethyl methacrylate) and MAPTMS (3-methacryloxypropyltrimethoxysilane). After organic polymerization, the obtained pHEMA-TiO2 and pMAPTMS-TiO2 hybrids are solids with different inter-component bindings. While surface exchange fixes organic (HEMA than pHEMA) groups on the nanoparticle surface, the titanium-oxo-alkoxo nanoparticles do not interact with the organic component in the pMAPTMS-TiO2 hydrid. Indeed, MAPTMS molecules are hydrolyzed forming condensed SiOSi species. The formation of SiOTi bonds is observed at the organic thermal polymerization stage, which may be a signature of the silica layer formation at the particles surface. Consequently, the quantum efficiency of the photoinduced charge separation and storage in pMAPTMS-TiO2 hybrids is found considerably lower compared to that in pHEMA-TiO2 hybrids. The 3D micro-structuring of the hybrid solutions has been realized using 2-photon laser polymerization. The structures were mechanically more stable and easier to achieve in pMAPTMS-TiO2 compared to pHEMA-TiO2 . Moreover, higher density of the photoinduced electrons decreases the damage threshold in the pHEMA-TiO2 hybrids.